Perfil epidemiológico y su relación con las barreras para acceso a trasplante renal de los pacientes con insuficiencia renal crónica atendidos en el hospital Manuel Ygnacio Monteros IESS Loja durante el año 2016 - Cabrera Jumbo, Jackson Marcelo (2018)
Abstract:The present research is a descriptive non-experimental, transversal and prospective study. Conformed by 43 patients with diagnosis of chronic renal failure, attended at the hospital Manuel Ygnacio Monteros IESS Loja during 2016. The patients were characterized. The inclusion and exclusion criteria given by INDOT were applied. After that knowledge, personal and barriers were determined in 23 patients who met the inclusion criteria. Statistical analysis performed with SPSS software. The results were: 52,2% female, 48,8% male, average age 60,26 years, cormorbility of IRC 68,1% diabetes mellitus, 88,4% hypertension. 56% was medically eligible to be a renal transplant recipient. The 33, 3% didn t receive information on the requirements and procedures necessary to be an organ recipient, the 37,5% don´t know the advantages of renal transplantation vs hemodialysis, the 33% don´t accept the transplant for fear of dying, economic conditions, and fear of perioperative complications of them, 100% have an economic impossibility to perform the kidney in a private hospital, 75% don´t go to specialized centers for transplant.